Information and cognitive technologies in the management of the quality of life through investments in the AIC: formal statement of the problem - T. P. Baranovskaya; E. V. Lutsenko (Новые технологии, 2018)
The article is devoted to cognitive structuring and formal problem statement for creating a system-cognitive model of the impact of investments in the agro-industrial complex on the quality of life. At the same time, the object and purpose of management and controlling factors will be determined, reference books of the future states of an object of modeling and factors affecting it will be developed, the source data will be coded and a training sample will be formed.